2020
DOI: 10.18549/pharmpract.2020.1.1682
|View full text |Cite
|
Sign up to set email alerts
|

Differences between pharmacists’ perception of counseling and practice in the era of prescription drug misuse

Abstract: Objective: This study was conducted to assess pharmacists' practices when counseling patients on their prescription medications, and their preferences for training. Methods: Five focus group discussions of community pharmacists (n=45, with seven to eleven participants in each group) were conducted in a major metropolitan city in the southern United States. Participants were recruited via email using a list of community pharmacists provided by the Texas State Board of Pharmacy. All focus group discussions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…28 Pharmacists dispensing naloxone, with or without a prescription, should not assume that the patients have been given any proper training or counseling about its use. 19 Our study shows ndings that having a naloxone standing order in place may not be as bene cial as intended given the lack of knowledge by the people who distribute the medication.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…28 Pharmacists dispensing naloxone, with or without a prescription, should not assume that the patients have been given any proper training or counseling about its use. 19 Our study shows ndings that having a naloxone standing order in place may not be as bene cial as intended given the lack of knowledge by the people who distribute the medication.…”
Section: Discussionmentioning
confidence: 79%
“…10-13,13−18 Pharmacists are well positioned to identify patients on high opioid dosages who would bene t from having naloxone on hand, to dispense naloxone, and to counsel patients accurately on its usage and overdose signs and symptoms. 9,13,14,17,19 All 50 states have passed laws increasing access to naloxone, although speci c access conditions vary by state. 20 Forty-two states as well as the District of Columbia allow the over-the-counter purchase of naloxone without the requirement of a prescription from a primary healthcare provider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that increased public awareness and increased pharmacist knowledge and training would be beneficial for increasing access to naloxone and potentially reducing opioid-related deaths [ 11 – 19 ]. Pharmacists are well positioned to identify patients on high opioid dosages who would benefit from having naloxone on hand, to dispense naloxone, and to counsel patients accurately on its usage and overdose signs and symptoms [ 10 , 14 , 15 , 18 , 20 ]. Recent policies passed by the American Pharmacists Association House of Delegates “supports access to third-party prescriptions for opioid reversal agents”; “supports the education for pharmacists … [on] the appropriate use of opioid reversal agents in overdose”; and “supports the pharmacist role in … providing education about the proper use of opioid reversal agents to prevention opioid-related deaths due to overdose.” [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…All 50 states have mechanisms by which pharmacists can directly dispense naloxone to patients without a prescription from a physician, although specific access conditions vary by state [ 22 – 24 ]. Forty-two states as well as the District of Columbia allow the purchase of naloxone without the requirement of a prescription from a primary healthcare provider [ 5 , 20 ]. A 2020 study found that adequate funding and staffing of local health departments and pharmacies, especially those in US counties with high rates of opioid overdose deaths, would be beneficial in supporting implementation of naloxone kit distribution and other opioid-related initiatives [ 8 ].…”
Section: Introductionmentioning
confidence: 99%